When E-Government Meets Local Reality: Rethinking Public Service Transformation in Disadvantaged Regions of Papua - Edyanto Edyanto; Hermanu Iriawan; Asmadianto Asmadianto (Universitas Teuku Umar, 2026)
This study examines how e-government initiatives interact with local realities in shaping public service transformation in disadvantaged regions, focusing on Biak Numfor Regency, Papua. It aims to rethink dominant assumptions of digital governance by analyzing how cultural, institutional, and infrastructural constraints affect implementation outcomes. Employing a qualitative case study approach, the research draws on in-depth interviews, field observations, and policy document analysis, particularly in licensing services. The findings reveal four interrelated challenges. First, cultural factors limit citizens’ adaptation to digital services, as many users remain unfamiliar with online applications and prefer face-to-face interactions. Second, limited human resource capacity—both in number and digital competence—constrains service responsiveness. Third, inadequate and costly infrastructure hampers the effective deployment of e-government systems. Fourth, uneven internet access creates significant disparities in service reach, particularly in remote island areas. These conditions demonstrate that digital transformation is not merely a technical process but deeply embedded in socio-cultural and territorial contexts. The study concludes that public service transformation in disadvantaged regions requires a shift from standardized digital reforms toward context-sensitive governance. It proposes a localized, hybrid approach that integrates cultural values, strengthens human resource capacity, and expands infrastructure through multi-sector collaboration. By foregrounding local realities, this research contributes to a more inclusive and grounded understanding of e-government implementation in the Global South.